2008
DOI: 10.1007/s00213-008-1403-5
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations for the quantification of self-reported caffeine use

Abstract: Rationale-The field of research regarding the effects of habitual caffeine use is immense and frequently utilizes self-report measures of caffeine use. However, various self-report measures have different methodologies, and the accuracy of these different methods has not been compared.Materials and methods-Self-reported caffeine use was estimated from two methods (a retrospective interview of weekly caffeine use and a 7-day prospective diary; n=79). These estimates were then tested against salivary caffeine co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…Drivers were asked to describe consumption patterns over that month, in quantity and frequency. Amounts consumed were described in an open ended format and then coded based on guidelines developed by Addicott and colleagues, 25 such that a "cup of coffee" or a "can of energy drink" contained 100 mg of caffeine and a cup of tea or can of caffeinated soft drink contained 50 mg of caffeine. Caffeine tablets purchased over the counter contain 100 mg per tablet and were therefore coded as such.…”
Section: Measurement Of Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Drivers were asked to describe consumption patterns over that month, in quantity and frequency. Amounts consumed were described in an open ended format and then coded based on guidelines developed by Addicott and colleagues, 25 such that a "cup of coffee" or a "can of energy drink" contained 100 mg of caffeine and a cup of tea or can of caffeinated soft drink contained 50 mg of caffeine. Caffeine tablets purchased over the counter contain 100 mg per tablet and were therefore coded as such.…”
Section: Measurement Of Risk Factorsmentioning
confidence: 99%
“…Low caffeine users consumed less than 200 mg a day, moderate caffeine users 200-400 mg a day, and high caffeine users more than 400 mg a day. 25 substances such as "speed" (amphetamine), cocaine, and ecstasy (3,4 methylenedioxymethamphetamine). If drivers said they had used any of these substances they were then asked further detail about the frequency and amount over the same period.…”
Section: Measurement Of Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple regression analyses reported here entered caffeine intake on an interval scale and retained the main findings of the preceding categorical analyses. Studies of the validity of self-reported caffeine intake suggest that in the normal range of caffeine intake (< 1200 mg/daily), these questionnaire methods are valid, but when higher intakes are reported, other supportive measures are required to corroborate this estimation [29].…”
Section: Auditory Verbal Learningmentioning
confidence: 99%